1993
DOI: 10.1172/jci116583
|View full text |Cite
|
Sign up to set email alerts
|

Vagal afferent pathway mediates physiological action of cholecystokinin on pancreatic enzyme secretion.

Abstract: To establish the mechanism(s) and site(s) of action of cholecystokinin (CCK) on pancreatic secretion under physiological conditions, we used an in vivo model using anesthetized rats with pancreaticobiliary cannulas. Infusion of CCK-8 (10-160 pmol/kg per h) produced a dose-dependent increase in plasma CCK levels. CCK-8 infusion at 40 pmol/kg per h produced a plasma CCK level of7.9±1.5 pM and an80% increase in pancreatic protein output over basal. This level was closely approximated by a postprandial peak plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
133
1
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 25 publications
17
133
1
3
Order By: Relevance
“…CCK is involved in the endocrine cells in the upper small intestine, principally acting to stimulate gallbladder contractions [34] and pancreatic secretion [35] , and to delay gastric emptying after meals [26] . Evidence has shown that CCK, stimulated by nutrients, is a physiological mediator which inhibits gastric emptying and subsequently suppresses food intake [26] .…”
Section: Discussionmentioning
confidence: 99%
“…CCK is involved in the endocrine cells in the upper small intestine, principally acting to stimulate gallbladder contractions [34] and pancreatic secretion [35] , and to delay gastric emptying after meals [26] . Evidence has shown that CCK, stimulated by nutrients, is a physiological mediator which inhibits gastric emptying and subsequently suppresses food intake [26] .…”
Section: Discussionmentioning
confidence: 99%
“…The relative contribution of these mechanisms may depend on the stage of postnatal development of the duodenum and pancreas (Biernat et al 1999). Studies in anaesthetised rats with CCK peptide and CCK 1 receptor antagonists administrations showed similar results (Li & Owyang, 1993, 1994, leading to a conclusion that in physiological conditions the prandial secretory response of the exocrine pancreas is chiefly driven by a neurohormonal mechanism, and a direct interaction of CCK with CCK 1 receptor on pancreatic acini is just a pharmacological effect (Owyang, 1996).…”
Section: Global Effects Of Gastrin and Cholecystokinin In The Gutmentioning
confidence: 97%
“…Recently, a new indirect mechanism of CCK action on pancreatic juice secretion has been postulated in preruminant calves [146,148] as well as in pigs and rats [64,83,145] [147,149]. The presence of CCK receptors in the small intestinal mucosa has been reported in rats and ferrets [6,88].…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%